REFERENCE EVAPOTRANSPIRATION BY PENMAN–MONTEITH FAO 56 WITH MISSING DATA OF GLOBAL RADIATION - de Souza, A. P.; Tanaka, A. A.; da Silva, A. C.; Uliana, E. M.; de Almeida, F. T.; Gomes, A. W. A.; Klar, A. E. (Revista Brasileira de Engenharia de Biossistemas, 2016)
The aim of this study was to evaluate the errors generated on the reference evapotranspiration (ET0) estimation by Penman-Monteith FAO 56 (PMF 56) when employed simplified models to estimate the global radiation (HG) are based on the air temperature. We evaluated 28 automatic weather stations (EMA’s) belonging to the National Institute of Meteorology (INMET) network, in different biomes of Mato Grosso state. Was evaluated fifteen simplified models of HG estimate calibrated regionally and five models without calibration. It was used as a reference ETo obtained by PMF 56, with HG measure. The statistical performance were employed mean bias error (MBE), root mean square error (RMSE), adjustmentindex (d) and the cumulative numerical order of the different models in each index. The regional calibration models HG estimation models improve the estimates of ETo. Can be used Bristow and Campbell (1984) and Goodin et al. (1999), De Jong and Stewart (1993) models to HGestimates and then ET0 to Amazon, Cerrado and Pantanal, respectively.